Evolutionary Programs in the Optimization of Cementless Hip Prosthesis - Bauer, J.; Pyrz, M. (Engineering Transactions, 2001)
The optimal design of cementless hip prosthesis is investigated in the paper. Design variables are materials (represented by their Young's moduli) of the non-homogenous stem prosthesis, disposed in vertical layers. The minimisation of the interface stress function with constraints on the resorbed bone mass fraction is presented. A simplified two-dimensional FEM model of a stem-bone configuration is considered, enabling however to obtain essential characteristics of the stem-bone load-transfer mechanism. Evolutionary algorithm approach is applied to find the optimal solution.